4,4′-(Pyrrolo[3,2-b]pyrrole-1,4-diyl)dianiline - Lorenza Giordano; Rafael Ballesteros; Rafael Ballesteros-Garrido (Molbank, 2020)
4,4′-(Pyrrolo[3,2-b]pyrrole-1,4-diyl)dianiline was synthesized in one step from benzene-1,4-diamine and ethylene glycol with Pd/Al2O3 and ZnO. The title compound was characterized by means of NMR techniques and HRMS mass spectrometry.